Efektivitas Metode Pembelajaran terhadap Pengetahuan Keamanan Pangan Siswa Sekolah Tingkat Menengah - Yanti Ratnasari; Rahmawati Rahmawati; Winiati P Rahayu (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2019)
Food safety education program needs to be given to the high school community, especially for junior and senior high school students who are entering adolescence. Appropriate learning methods required in the delivery of food safety information. The aim of this study was determining the effect of the way food safety intervention with active and passive learning method to the food safety knowledge of high school students. Analysis of different test with independent t-test on both active and passive learning methods of intervention showed there was no different between both methods. The result of the effect of food safety intervention with active and passive learning methods by paired sample t-test showed increasing the average score of food knowledge (p≤0.05) between before and after the intervention of 2.18 and 2.54 %. Based on the distribution of score of knowledge, active learning method just increased significantly only for senior high school students in science program. Correlation analysis showed the higher school level did not ensure higher food safety knowledge as well.